The main determinants effecting international visitor arrivals in New Zealand: Some empirical evidence. Issue 5 (August 2017) - Gani, Azmat; Clemes, Michael D.
This study examines the main determinants of international visitor arrivals in New Zealand in light of New Zealand's major earthquakes in 2010 and 2011 as well as the global financial crisis of 2007. Our results provide strong evidence that visitor origin country per capita incomes, relative prices, real exchange rates, the distance between New Zealand and its main visitor origin countries and New Zealand's record of good governance are statistically significant determinants of visitor arrivals to New Zealand. Our findings also reveal a negative but statistically insignificant effect of the earthquakes of 2010 and 2011on visitor arrivals to New Zealand. Our findings do not provide any significant regressive effect of the global financial crisis on visitor arrivals to New Zealand.